The Naples prognosis score as an independent predictor of sepsis-associated acute kidney injury: a retrospective cohort study - Hong, Hao; Kong, Jindan; Wei, Yao; Jin, Jun; Liu, Xueke (Frontiers in Medicine, 2026)
ObjectiveThis study aimed to evaluate the predictive efficacy of the Naples prognosis score (NPS) in sepsis-associated acute kidney injury (SA-AKI) and explore its mechanistic link to renal injury, with the goal of providing a novel clinical tool for early SA-AKI risk assessment.MethodsOne-way ANOVA was applied to variables exhibiting normal distribution and homo-geneous variance. Spearman analysis was performed to assess relationships. Non-normal distribution variables were analyzed using the rank sum test. Binary and ordered logistic regression analyses were conducted to evaluate independent relationships with SA-AKI. Receiver operating characteristic (ROC) curve was employed to determine diagnostic accuracy. The survival curve was plotted by Kaplan Meier.ResultsThe NPS score was significantly higher in the SA-AKI group than in the non-AKI group (P < 0.001). Multivariate logistic regression showed that NPS was an independent predictor of SA-AKI (OR = 11.777, P < 0.001), with an area under the ROC curve (AUC) of 0.855. Correlation analysis indicated positive associations of NPS with renal injury markers (urea nitrogen, serum creatinine, cystatin C) and negative associations with platelet count and low-density lipoprotein. Subgroup analyses demonstrated that NPS effectively predicted SA-AKI regardless of vasopressor use or continuous renal replacement therapy (CRRT), with AUC values of 0.898 in the vasopressor group and 0.866 in the non-CRRT group.ConclusionNaples prognosis score serves as an independent predictor of SA-AKI, integrating inflammatory, nutritional, and metabolic markers to provide new insights into SA-AKI pathophysiology. Clinically, NPS offers a simple and feasible tool for early identification of high-risk SA-AKI patients, guiding personalized treatment strategies.